Religion, Female Sexuality and Magic in (Post)Modern Film - Vinczeová, Barbora (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The paper strives to investigate the relationship of female sexuality, magic and religion in film based on the comparison of two selected films. The three themes have been often seen as intertwined especially by religion, which has built an image of a female witch in alliance with the devil, or evil forces. The research aims to answer the question whether postmodern cinema embraces the combination of the aforementioned themes often associated, historically, with the notion of witchcraft practised especially by female witches. The scope of the research is limited to two films; however, the possibility to expand the research in the future and include newer films exists. Comparative methods and analysis are used throughout the paper. The paper is structured according to the analysed themes found in both films – Carrie (dir. Kimberly Peirce, 2013) and Thelma (dir. Joachim Trier, 2017). The author claims that these themes are similar and rooted in the same perception of the female monstrosity in both films, with different outcomes of this combination. The authors suggest that this is due to feminist tendencies becoming more prominent in every artform. However, this claim needs investigating from the feminist studies’ point of view.